Recent Updates in HVAC Systems (IntechOpen, 2024)
This book focuses on heating, cooling, ventilation, and air conditioning systems, as well as the energy systems required for buildings not connected to thermal and electrical networks. However, it is essential to note that the book does not just discuss buildings in remote or challenging locations. Current society demands that future structures, regardless of whether they are newly constructed or renovated, not only meet the nearly zero energy building (nZEB) standards but also produce surplus energy. Concepts such as heat pumps, heat recovery, and energy efficiency, in addition to artificial intelligence, cryptocurrency mining, and exergy, will undoubtedly provide high-value solutions to both new and refurbished buildings.